Savings, Child Support, Pensions and Endogenous (and Heterogeneous) Fertility - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
van Groezen, Leers and Meijdam (2003) (for short, GLM) analyzed combination of public pension and child support in an OLG model. We impose credit constraint on workers, and extend GLM's analysis from the case where workers do not understand the cost also to the case where they do. GLM's infinite stream of generations is simplified into three generations but heterogeneity of rearing costs and of enjoying children is introduced. Two major results: (i) excluding negative savings, fertility decreases with pension contributions and increases with taxes; (ii) the introduction of fertility-dependent pensions may strengthen heterogeneity in fertility.
Keywords: D10; H55; J13; J14; J18; J26; 330; Child support; Endogenous fertility; Overlapping generations; Pensions